IRC online apps and information service (iOASIS) - Abdul Karim, Siti Nurbaya; Suito, Helmi Iskandar; Bidin, Mohd Faizal; Mohd, Kamaliah; Mahmud, Wan Normanizah (Universiti Teknologi MARA, Kedah, 2019)
The rapid progress of the internet upgrades the accessibility of information that enables people to acquire information faster, anytime and anywhere. However, there are only a few channels are available for the library’s users in acquiring the information, to say, either by asking through the circulation counter or the website. These conventional methods limit the patron in accessing the information in time. “Information at the fingertips” is the philosophy behind the development of the IRC Online Apps and Information Service (iOASIS) that aims to improve the accessibility of the information regarding library operation and services in a centralized manner. iOASIS is developed to act as an online hub that includes all information about library comprising of operation schedule, Online Public Access Catalog (OPAC), subscribed databases, institutional repository, interlibrary loan, OpenAthens, livechat, room booking, etc. The idea of minimalist design and user-friendly features concept has been used as a guide in developing the app which enable the users to understand and navigate the app easily. As a result, the iOASIS has been downloaded 501 times since its launch on 31st July 2018. An upgrade version of the app, called iOASIS 2.0 has been rolled out in September 2019, where IRC Augmented Reality (IRC AR) feature is consolidated into the apps, allowing an interactive search of IRC’s collections. To date, iOASIS has rated 4.47 over a total score of 5, which indicates an approval from the users to the introduction of the app. In conclusion, iOASIS has been successfully deployed to UTP students. It is proven that the app provides the patron with a hassle-free experience in acquiring the information which directly improves the rating of the library’s service.